2019
DOI: 10.21744/irjmis.v6n3.638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of budget participation towards regional government managerial performance

Abstract: This research was intended at examining the effect of budget participation towards managerial performance with organizational commitment, job-relevant information, organizational culture, and leadership style as moderating variables on local government in Sikka Regency, NTT. The questionnaire survey method was distributed to local government structural officials. The sampling technique was purposive sampling method. The data analysis technique used moderated regression analysis method. The results of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…[7]. This statement is also supported by [2] that budget participation will improve manager performance, this is confirmed by the results of the study [5], [8], [9] proves that budget participation has an effect on managerial performance. Based on the statements and results of previous research, the hypothesis is as follows: Ha1: There is an effect of budgeting participation on managerial performance b.…”
Section: Hypothesis Development a Effect Of Budget Participation On mentioning
confidence: 52%
“…[7]. This statement is also supported by [2] that budget participation will improve manager performance, this is confirmed by the results of the study [5], [8], [9] proves that budget participation has an effect on managerial performance. Based on the statements and results of previous research, the hypothesis is as follows: Ha1: There is an effect of budgeting participation on managerial performance b.…”
Section: Hypothesis Development a Effect Of Budget Participation On mentioning
confidence: 52%
“…The results of testing the second hypothesis have the same results with research conducted by Sumarno (2005), examining the influence of leadership style with the relationship between budgetary participation and managerial performance and found that leadership style has a positive effect on the relationship between budgeting participation and managerial performance. Different results found by Maharani (2010) & Romario et al, (2019, indicate that budgetary participation has a positive and significant effect on managerial performance but leadership style does not moderate the relationship between budgeting participation and managerial performance.…”
Section: The Effect Of Leadership Style Consideration In Moderating Tmentioning
confidence: 68%
“…At Denpasar KPPN the time needed to carry out the verification process up to conversion to SPAN for one bill is between 1 to 2 minutes for non-contractual SPM and 2 to 3 minutes for contractual SPAN. The problem at this stage is that sometimes the officers who deliver the bills do not understand the substitution of the bills, if there are problems they cannot provide an adequate explanation, this makes the service in the FO so hampered (Romario et al, 2019).…”
Section: Bill Adk Verification and Conversionmentioning
confidence: 99%